Proceedings of the 12th ACM Workshop on Multimedia and Security 2010
DOI: 10.1145/1854229.1854268
|View full text |Cite
|
Sign up to set email alerts
|

Simple algorithmic modifications for improving blind steganalysis performance

Abstract: Most current algorithms for blind steganalysis of images are based on a two-stages approach: First, features are extracted in order to reduce dimensionality and to highlight potential manipulations; second, a classifier trained on pairs of clean and stego images finds a decision rule for these features to detect stego images. Thereby, vector components might vary significantly in their values, hence normalization of the feature vectors is crucial. Furthermore, most classifiers contain free parameters, and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…We note that the bootstrap samples are formed "by pairs," i.e., we make sure that the pairs of cover features and the corresponding stego features are preserved. This modification, which is specific for steganalysis, is rather important as it has been shown that breaking the coverstego pairs into two sets, one of which is used for training and the other, testing, one for error estimation, may lead to a biased error estimate and, consequently, to a suboptimal performance [46], [27].…”
Section: A the Ensemblementioning
confidence: 99%
“…We note that the bootstrap samples are formed "by pairs," i.e., we make sure that the pairs of cover features and the corresponding stego features are preserved. This modification, which is specific for steganalysis, is rather important as it has been shown that breaking the coverstego pairs into two sets, one of which is used for training and the other, testing, one for error estimation, may lead to a biased error estimate and, consequently, to a suboptimal performance [46], [27].…”
Section: A the Ensemblementioning
confidence: 99%
“…The training set is formed by pairs of cover features and the corresponding stego features, extracted as differences with respect to their smoothed versions. This is quite important as it has been shown that breaking the cover-stego pairs may lead to a suboptimal performance [16]. Furthermore, training the classifier is a crucial issue, as the steganalyzers trained by different machine learning methods will show different performances.…”
Section: D Steganalysis Frameworkmentioning
confidence: 99%
“…The classification was done with a 1-norm soft margin non-linear C-SVM classifier using a Gaussian kernel. The choice of the parameter C of the SVM and the width σ of the Gaussian kernel was based on the paired cross-validation procedure described in [13].…”
Section: Spam Features Type Steganalyzermentioning
confidence: 99%